Comparative genomics using long-read sequencing identifies nearly identical TAL effector regions in two Xanthomonas oryzae pv. Oryzae isolates collected from the basmati rice-growing region of Pakistan - Ejaz, Khansa; Zakria, Muhammad; Zhang, Peiqi; Huguet Tapia, Jose; Arif, Muhammad; White, Frank; Yasmin, Sumera (Frontiers in Microbiology, 2025)
The emergence of hostile and novel plant pathogenic strains poses a serious threat to global food security, which renders the strategies for disease management in modern agriculture ineffective. Preventing the consequences of these emerging phytopathogens requires accurate genetic information about the pathogen population to formulate effective management strategies. Bacterial leaf blight (BLB), caused by Xanthomonas oryzae pv. oryzae (Xoo), is the foremost reason for substantial yield losses in rice crops worldwide, especially in Asia. The genetic information regarding the Pakistani Xoo population is still unexplored. To bridge this gap, two representative Pakistani Xoo isolates, namely PkXoo1 and PkXoo2, were sequenced using long-read Oxford Nanopore Technology (ONT). Both isolates were obtained from the Basmati rice-growing region of Pakistan, with substantially high virulence on certain susceptible rice varieties. The final assembly of PkXoo1 and PkXoo2 yielded a circular chromosome of approximately 4.9 MB with a G + C content of 64%. Genome annotation of both strains revealed the presence of key genes associated with hypersensitivity and virulence in Xoo. The AnnoTALE analysis showed that both strains contained 18 transcription activator-like (TAL) effectors, three of which were predicted to be pseudoTALes. A phylogenomic analysis grouped PkXoo1 and PkXoo2 with strains belonging to India and Thailand, placing them far apart from other major Asian Xoo strains. The present study revealed significant findings about the conservation of repeat variable di-residues (RVDs) in major TAL effectors and the utility of high-throughput sequencing technologies for TAL effector analysis and pathogen tracking. The complete genome sequence of Xoo isolates from Pakistan will enhance sequence resources for the global comparison of Xoo diversity across the region. This information is also of great significance for launching effective and durable breeding programs.